The Influence of Workload and Organizational Commitment On Performance of Non-Medical Employees at Syafira Hospital Pekanbaru - Sulvitri, Vinda; Syaifora, Loveana; Haznil, Alief Feisal; Susanti, Roza Sri (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to examine and analyze the effect of workload and Organizational Commitment On Performance of Non-Medical Employees at Syafira Hospital, Pekanbaru City. This research includes quantitative research. The population of this study was 224 non-medical employees of Syafira Hospital, Pekanbaru City, with 69 people being used as samples determined using the slovin formula. Data collection techniques in this study using a questionnaire. The data analysis technique in this study used quantitative descriptive analysis and used SPSS 21. The results of this study indicate that workload and organizational commitment partially and simultaneously have a positive and significant effect on performance of non-medical employees at Syafira Hospital, Pekanbaru City. The most dominant variable affecting on performance of non-medical employees in this study is organizational commitment variable. Meanwhile, the influence of of workload and organizational commitment on performance is shown by the R-Square result of .91,5%.